2016
DOI: 10.1016/j.jconrel.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a synthetic TLR7/8 ligand to aluminum oxyhydroxide for enhanced vaccine adjuvant activity: A formulation approach

Abstract: For nearly a century, aluminum salts have been the most widely used vaccine adjuvant formulation, and have thus established a history of safety and efficacy. Nevertheless, for extremely challenging disease targets such as tuberculosis or HIV, the adjuvant activity of aluminum salts may not be potent enough to achieve protective efficacy. Adsorption of TLR ligands to aluminum salts facilitates enhanced adjuvant activity, such as in the human papilloma virus vaccine Cervarix®. However, some TLR ligands such as T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 25 publications
4
61
0
Order By: Relevance
“…The strong adjuvanticity of 3M‐052 exhibited in our study was also observed in other reports in which 3M‐052 was formulated into vaccines using lipid‐based or combined lipid‐Alhydrogel® delivery platforms. Fox et al reported that a liposome‐Alhydrogel® formulation with 3M‐052 enhanced the antigen‐specific IgG1 and IgG2c titers and frequency of T H 1 cytokine‐producing CD4 + memory cells of a tuberculosis vaccine in mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strong adjuvanticity of 3M‐052 exhibited in our study was also observed in other reports in which 3M‐052 was formulated into vaccines using lipid‐based or combined lipid‐Alhydrogel® delivery platforms. Fox et al reported that a liposome‐Alhydrogel® formulation with 3M‐052 enhanced the antigen‐specific IgG1 and IgG2c titers and frequency of T H 1 cytokine‐producing CD4 + memory cells of a tuberculosis vaccine in mice.…”
Section: Discussionsupporting
confidence: 88%
“…To address this limitation, the lipophilic derivative 3M‐052 was developed as a next‐generation TLR7/8 agonist that is retained at the injection site longer . Because of the lipophilic nature of 3M‐052, liposomes or other lipid‐based delivery vehicles have been used for subcutaneous, intramuscular, or intratumoral injections of 3M‐052 …”
Section: Introductionmentioning
confidence: 99%
“…S2B). Accumulating evidence suggests that tissue retention is an indispensable characteristic for TLR7 agonist function as a vaccine adjuvant [25,26]. To test the activity of T7-EA in vivo, we injected 35 nmol T7-EA, T7, R848 or normal saline in the gastrocnemius muscles [intramuscular (i.m.)]…”
Section: T7-ea Is a Tlr7-selective Agonist That Induces Local Cytokinmentioning
confidence: 99%
“…The number of immunostimulatory agonists targeting PRR in recombinant antigenic peptide vaccines is increasing [59]. Anti-tuberculosis vaccines have used a diverse array of molecular adjuvants directed against multiple Toll-like receptors (TLR) and have elicited a surprisingly diverse set of responses [5966].…”
Section: Adjuvantsmentioning
confidence: 99%
“…Anti-tuberculosis vaccines have used a diverse array of molecular adjuvants directed against multiple Toll-like receptors (TLR) and have elicited a surprisingly diverse set of responses [5966]. Comparative analysis between novel adjuvants and BCG suggests that stimulation of antigen presenting cells via a single PRR may in some cases be sufficient to induce activated T cells [21].…”
Section: Adjuvantsmentioning
confidence: 99%